A (socio) economic analysis of doping in elite sport (2002)
There have always been reasons to cheat in sport. One of the ways to cheat has been to use drugs, and the main reason to cheat has always been the eagerness to win. The world of sport, however, is changing and the The European Commission (EC) would like to understand new developments in the sport environment that might explain the recent rise of doping-related scandals. The EC supports the fight against doping use in many ways. To guide its anti-doping policy, the EC initiated a study into the structural causes explaining the rise in doping practices in sport. To answer this question, the Directorate General of Education and Culture of the European Commission assigned KPMG Economic Consulting (KPMG BEA) and the Asser Institute with the task to analyse the (socio-) economic causes of doping use. Focus of the study On the basis of today`s developments in sports we focussed on three specific factors likely to contribute to the rise in doping practices in sport. These factors are: - financial rewards in sport are getting more and more important. Who is pouring money into sport and why, and could this lead to a doping-prone environment? - the number of games and tournaments seems to be growing. Are the physical limits of the human body within reach, so athletes need doping to survive? - isn`t society changing in a way that our attitude towards doping use is changing? &RQFOXVLRQV Based on an extensive research, the reading of many relevant books and articles and interviews with a great number of experts in the field of sports, marketing, the media and health, KPMG BEA and Asser come to the following main conclusions: - sport is entertainment. Consumers seem to have an unlimited desire to watch, hear and read about top sports. This makes sport the ultimate communication vehicle for sponsors and the core business for many media companies. Media exposure attracts the attention of private sponsors and governments that invest a growing amount of money in sport. Due to the specific sportive-economic characteristics of the sports market, the money pouring into sport is distributed unequally among athletes, clubs, sports and events: just a few winners get it all. The increasing commercialisation adds strong (economic) pressure on athletes and clubs to get to (and stay at) the top. The commercialisation of sports and the increasing physical demands on athletes do indeed contribute to a doping-prone environment; - the old Olympic motto "Citius - Altius - Fortius - has never been as relevant as now. In the rat race to attract the attention of the viewers, sports have changed: more games and tournaments with more competition and excitement. The athletes and clubs are in the same race, as they need to maintain their market position in order to stay in the spotlight and earn a reasonable income. If they fail, others will take their place. With tough competition, power and strength are gaining importance at the cost of technique. In the end, elite sport is becoming physically more and more demanding. There are several ways to keep up with the competition and cope with the physical demands (stay in shape). More and better training, mental preparation, better food, technical innovation or doping use are the basic possibilities. As modern athletes are pushing themselves to their limits, they sometimes (have to) cross the border and use doping. The rules and regulations of sport federations are almost no hindrance whatsoever to the modern exaggeration of the modern Citius Altius Fortius. National legislation and `sports law` only incidentally contain provisions that are applicable to sport; - the commercialisation of sports has really picked up over the last decade, almost simultaneously with the apparent introduction of a new, more structured and scientific way of using performance-enhancing drugs and food supplements. KPMG therefore concludes that, besides the ever existing internal motivators, such as pride and self-esteem, the increasing economic pressure on athletes (and the resulting physical exhaustion) is and will be an important contributor to a doping-prone environment; - this is a valuable lesson for the fight against doping, as it offers the opportunity to use new instruments that effect the background of the apparently new form of structural doping use; - the attitude of society towards doping reveals a fair amount of hypocrisy. On the one hand, society shows a growing willingness to use powders and pills for health and good looks. On the other hand, we continue to condemn athletes taking substances to cope with the physical pressures of top sports. Physical pressures that, after all, society puts on them. 1 Introduction 1 1.1 Background 1 1.2 Methodology 1 1.3 Analytical framework 2 1.4 Structure of this report 4 2 Doping in sport 5 2.1 What is doping and why combat doping? 5 2.2 Who combats doping? 6 2.3 A brief history of doping in sport 7 3 The commercialisation of sports 9 3.1 Money, money, money…. 9 3.2 The mediasation of sports 11 3.3 The winner-take-all rat race 13 3.4 Conclusions 19 4 Citius Altius Fortius 21 4.1 The development of elite sports 21 4.1.1 More 21 4.1.2 Better 23 4.1.3 Consequences for the athlete 26 4.2 The role of performance-enhancing drugs 27 4.3 Conclusion 29 5 Which role does society play? 31 5.1 Changing attitude towards food and medication 31 5.2 Achievement-oriented society 34 5.3 Entertainment-oriented society 36 5.4 Conclusions 38 6 Legal analysis 39 6.1 Introduction 39 6.2 Analytical framework 41 6.3 National legislation of EU Member States 44 6.4 The applicability of general national legislation to sport 50 6.5 Self-regulation by national sports federations 50 7 Conclusions and recommendations 53 7.1 Conclusions 53 7.2 Recommendations and suggestions for further research 55 Annexes 63 A Literature 65 A.1 Media & economics 65 A.2 Citius Altius Fortius 66 A.3 Role of society 68 A.4 Legal 69 A.5 Miscellaneous 71 B List of people interviewed 73 C Research Team 77 D Factors that may contribute to doping use 79 E Micro analysis 81 E.1 Framework of the model 81 E.2 Data on doping use 81 E.3 Data on explanatory variables 87 E.4 A small model 87